CUTANEOUS METASTASES UNVEILING BREST CANCER – THERAPEUTIC AND DIAGNOSTIC CONSIDERATIONS - Florica Sandru; Mihai Cristian Dumitrascu; Aida Petca; Raluca Gabriela Miulescu; Tiberiu Tebeica; Adelina Popa (Journal of Surgical Sciences, 2020)
Metastatic cutaneous lesions are seen more commonly in breast cancer than in any other malignancy in women. Secondary breast cancer happens when cancer cells spread from the breast to other parts of the body. Sometimes breast cancer cells can spread to the skin. This can happen through the blood or lymphatic system. The presence of skin metastases signifies widespread systemic disease and a poor prognosis. The chest wall, the abdomen, the back, and the upper extremities are common sites.We present the case of a 69-year-old woman presented to our Surgery Department in June 2019, after appearing in the Dermatology Department a week ago, for the appearance of multiple subcutaneous painless, hardened, skin-colored nodules spread to the cervical region, anterior chest walls and upper limbs. Anatomopathological examination of the skin biopsy, performed on the anterior face of the left arm, showed dermal fragment with neoplastic, suggestive for lobular breast carcinoma (stage IV). The patient was referred to the oncological surgery department where our patient underwent a left total mastectomy and sentinel lymph node biopsy. The technique of mastectomy was the Madden technique. The surgery has no healing character, being more a necessity intervention that seeks to avoid the complications of the local evolution of the disease, such as ulceration, hemorrhage or suppuration, the possibility of applying the other forms of treatment (radiotherapy and / or polychemotherapy), elimination of a source of permanent metastatic sowing thus leading to more efficient treatment.